Molecular characterization of calponin-2, an immune-related gene in snakehead fish, channa striata / Nurul Irda Yanti Ku Zubir - Nurul Irda Yanti, Ku Zubir (2016)

(untitled)
Channa striata, locally known as “snakehead fish” is an important commercial freshwater fish in Southeast Asia. While highly immune to common diseases affecting commercial fishes, recent reports have shown that C. striata are prone to the disease Epizootic Ulcerative Syndrome (EUS). Control of EUS is associated with immune responsive genes. In this study, it is suggested that calponin-2 is a potential immune-related gene (designed as CsCalp) that plays a functional role during EUS infection in snakehead fish. The full-length cDNA of the CsCalp is 1114 base pairs (bp) long, containing a 5´ untranslated region (UTR) of 104 bp, a 3‟ UTR of 56 bp including a stop codon (TAA), and an open reading frame (ORF) of 954 bp encoding 317 amino acids with the predicted molecular mass of 35.14 kDa and an estimated isoelectric point of 6.15. Sequence analysis showed that calponin has a calponin homology domain and calponin-like repeats. Quantitative real-time PCR analysis showed ubiquitous expression of CsCalp in all the C. striata tissues tested with the highest expression level in the blood. Preliminary analysis of CsCalp expression in blood challenged with Aeromonas hydrophila showed significant (P<0.05) changes in the gene regulation. As time progressed, the expression level of CsCalp increased significantly and reached the maximum at 24 h after the A. hydrophila challenge. The results indicated that CsCalp gave positive response towards bacterial infection in C. striata. CsCalp was then directly cloned into the TOPO expression vector, pTrcHis® TOPO in the E. coli system. This construct, however, failed to give significant expression of recombinant CsCalp. Nevertheless, these findings should be further investigated for downstream functional studies of calponin-2 in the snakehead fish immune system.